PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN PADA @BASOACICUANKIAA DI SEPATAN TANGERANG - Johan Johan; Maradonald Maradonald; M. Rachman Mukyandi (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2022)
In the era of globalization, technology has developed very rapidly, one of which is the internet. The development of technology is currently a means to promote in business, one of the current marketing techniques is social media marketing, where a company promotes through the digital world to make buying and selling transactions that are believed to be able to influence to attract and increase consumer buying interest in an item. or services offered by the seller. This study uses qualitative methods with research data from secondary sources, namely library research. Literature review is used in this study as a data collection technique. Data analysis techniques are carried out by reducing data, presenting data and drawing conclusions from the data that has been obtained. The object of this study was consumers and Instagram followers @basoacicuankiaa who live in Tangerang. The independent variables of this study are context (X1), communication (X2), collaboration (X3), and connection (X4) and the dependent variable in this study is buying interest (Y). Based on the results of the study, it was found that context, communication, collaboration, and connection were found to have an influence on buying interest